Somatic POLE exonuclease domain mutations are early events in sporadic endometrial and colorectal carcinogenesis, determining driver mutational landscape, clonal neoantigen burden and immune response. Issue 3 (30th April 2018) - Temko, Daniel; Van Gool, Inge C; Rayner, Emily; Glaire, Mark; Makino, Seiko; Brown, Matthew; Chegwidden, Laura; Palles, Claire; Depreeuw, Jeroen; Beggs, Andrew; Stathopoulou, Chaido; Mason, John; et al.
Abstract: Genomic instability, which is a hallmark of cancer, is generally thought to occur in the middle to late stages of tumourigenesis, following the acquisition of permissive molecular aberrations such as TP53 mutation or whole genome doubling. Tumours with somatic POLE exonuclease domain mutations are notable for their extreme genomic instability (their mutation burden is among the highest in human cancer), distinct mutational signature, lymphocytic infiltrate, and excellent prognosis. To what extent these characteristics are determined by the timing of POLE mutations in oncogenesis is unknown. Here, we have shown that pathogenic POLE mutations are detectable in non‐malignant precursors of endometrial and colorectal cancer. Using genome and exome sequencing, we found that multiple driver mutations in POLE‐ mutant cancers show the characteristic POLE mutational signature, including those in genes conventionally regarded as initiators of tumourigenesis. In POLE‐ mutant cancers, the proportion of monoclonal predicted neoantigens was similar to that in other cancers, but the absolute number was much greater. We also found that the prominent CD8 + T‐cell infiltrate present in POLE ‐mutant cancers was evident in their precursor lesions. Collectively, these data indicate that somatic POLE mutations are early, quite possibly initiating, events in the endometrial and colorectal cancers in which they occur. The resulting early onset of genomic instability may account for the striking immune response and excellent prognosis of these tumours, as well as their early presentation. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.